Studies on electroless nickel boride coating on boron carbide particles. (October 2014) - Deepa, J. P.; Rajan, T. P. D.; Pavithran, C.; Pai, B. C.
Abstract : Ni–B alloy deposits were successfully formed over alkali surface treated boron carbide by electroless technique and the effects of processing parameters such as reduction bath pH, temperature and post-heat treatment were investigated. Microstructural studies show remarkable changes in structural morphology from mesh-like structure to platelet type Ni–B coating. The main Ni–B phases observed were NiB, Ni2 B, Ni3 B and Ni4 B3 . An effective Ni–B alloy coating with better surface characteristics was formed at pH 8 under 75°C reaction bath temperature in the presence of bath stabiliser. The post-heat treatment of Ni–B coated particles under varying bath reaction temperatures at 400°C showed remarkable Ni–B phase transformation from metastable NiB and Ni2 B to stable crystalline Ni3 B phase. The NiB coated particle shows lower particle–matrix interfacial reaction, better wettability and enhanced dispersion in aluminium composites compared to uncoated particles.